2008
DOI: 10.1111/j.1440-1797.2008.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for quality of life in continuous ambulatory peritoneal dialysis patients

Abstract: Poor sleep quality, presence of depression, higher C-reactive protein and lower albumin levels are associated with poorer quality of life. In order to improve life quality in CAPD patients, quality of sleep, depression and nutritional status should be serially evaluated and given appropriate treatment when required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
3
17
0
Order By: Relevance
“…Data reported from different countries show that the HRQoL assessment outcomes ranged from poor to moderate. 4,13,19,[22][23][24]29,[31][32][33] MCS and PCS scores in our study were similar to those in studies reported from Serbia, France, and Mexico. 2,28,30 However, MCS in our study was slightly lower than that of the United Kingdom, the United States, and the Netherlands, whereas PCS was higher than that of the United Kingdom and the United States.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Data reported from different countries show that the HRQoL assessment outcomes ranged from poor to moderate. 4,13,19,[22][23][24]29,[31][32][33] MCS and PCS scores in our study were similar to those in studies reported from Serbia, France, and Mexico. 2,28,30 However, MCS in our study was slightly lower than that of the United Kingdom, the United States, and the Netherlands, whereas PCS was higher than that of the United Kingdom and the United States.…”
Section: Discussionsupporting
confidence: 89%
“…1,19,30 Previous studies using the SF-36 scale in Turkey have shown that the PCS and MCS scores were higher than ours. 20 On the contrary, our scores are similar to Bilgiç et al 31 Similarities may have originated from the sampling groups in both studies with regard to mean age and PD duration of the patients. The difference may be the result of the lower PD duration in the study by Kalender et al 20 than in ours.…”
Section: Discussionsupporting
confidence: 71%
“…Concerning factors that influence HRQOL in PD patients specifically, Bakewell et al showed a decline of HRQOL over time that was associated with poorer clinical outcomes (12). Other factors affecting this group of patients are low residual renal function (13,14), malnutrition, and inflammation (15). Depression and anxiety have also been reported as being a problem in PD patients, affecting their assessment of their own HRQOL (16)(17)(18).…”
Section: Rossi Dos Santos Grincenkov Et Almentioning
confidence: 99%
“…In a study that aimed to determine the clinical, biochemical and psychological predictors of HRQOL in PD patients, Bilgic et al [6] observed that depression, poor sleep, high C-reactive protein and low albumin levels were associated with worse HRQOL in a group of 60 PD patients, suggesting that interventions targeted to improve these parameters should be prioritized. Moreover, these data reinforce the needs to identify the factors which may negatively impact the QOL of these patients and address them.…”
Section: Introductionmentioning
confidence: 99%